An Improved Model of Moderate Sleep Apnoea for Investigating Its Effect as a Comorbidity on Neurodegenerative Disease - Roberts, Reno; Wall, Mark J.; Braren, Ingke; Dhillon, Karendeep; Evans, Amy; Dunne, Jack; Nyakupinda, Simbarashe; Huckstepp, Robert T. R. (Frontiers in Aging Neuroscience, 2022)
Sleep apnoea is a highly prevalent disease that often goes undetected and is associated with poor clinical prognoses especially when its combined with many different disease states. However, most animal models of sleep apnoea (e.g., intermittent hypoxia) have recently been dispelled as physiologically unrealistic and are often unduly severe. Due to a lack of appropriate models, little is known about the causative link between sleep apnoea and its co-morbidities. To overcome these problems, we have created a more realistic animal model of sleep apnoea of a moderate phenotype by reducing the excitability of the respiratory network. This has been achieved through controlled genetically mediated lesions to the preBötzinger Complex (preBötC), the inspiratory oscillator. This novel model shows increases in sleep disordered breathing with alterations in breathing during wakefulness (decreased frequency and increased tidal volume) as observed clinically. The increase in apnoea episodes leads to a reduction in REM sleep, with all lost active sleep being spent in an awake state. The increase in hypoxic and hypercapnia insults leads to both systemic and neural inflammation. Alterations in neurophysiology, an inhibition of hippocampal long-term potentiation (LTP), reflect deficits in both long- and short-term spatial memory. This improved model of moderate sleep apnoea may be the key to understanding why sleep apnoea has such far reaching and often fatal effects on end organ function.